Onomatopoeia in Hajime Isayama's Attack on Titan Manga - Rahmi, Syiffa Salama; Maulidia, Iska Nisrina; Salsabila, Mega Ganevia; Naddindra, Athaya; Sujatna, Eva Tuckyta Sari (DBSMB, Vocational College of Universitas Gadjah Mada, 2024)
This research aims to describe the different types of onomatopoeia in Hajime Isayama’s Attack on Titan Volume 1 manga. Attack on Titan is the English title of the Japanese manga series Shingeki no Kyojin, written by Hajime Isayama. The researchers selected Attack on Titan Volume 1 manga as the object of study because the plot in the early beginning of the story uses various onomatopoeic words to enhance the action scenes and intensity of the battles. This research uses a descriptive qualitative approach to describe the types of onomatopoeia using the theory stated by Bredin (1996). The data were collected by reading all the chapters in Attack on Titan volume 1 manga, taking notes of the onomatopoeias found throughout the story, and identifying their type and function. The findings of this research show that 99 data of onomatopoeic words are found in the manga, consisting of 55 direct onomatopoeia, 14 associative onomatopoeia, and 32 exemplary onomatopoeia. Direct onomatopoeia appeared more frequently than the other two forms because many character movements and natural sounds happen throughout the story.